Examining the Readiness of the Organization's Security Success in Improving Security Performance - Zuhroh, Nur Fatimatuz; Baihaqy, Ahmad (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Information security has become an important issue in the digital era due to increased cyber threats and data leaks. This study analyzes the influence of Organizational Culture, Risk Propensity, and Security Readiness on Organizational Security Performance, with Top Management Support as the moderation variable. This study uses a quantitative method with a survey approach and is analyzed using SPSS software for regression, mediation, and moderation tests. The results show that Organizational Culture, Risk Propensity, and Security Readiness have a significant influence on Organizational Security Performance. Security Readiness is proven to be a mediating variable that strengthens the relationship between Organizational Culture and Risk Propensity to organizational security performance. In addition, Top Management Support acts as a moderator that strengthens the relationship between independent variables and Organizational Security Performance. This research contributes by integrating Security Readiness as a mediator and Top Management Support as a moderator in the information security framework. These findings highlight the importance of a holistic approach that includes organizational culture, risk behavior, security readiness, and top management support to improve information security resilience amid the challenges of the digital age and the result can be a recommendation for the government and private sectors.